Characteristics of Risk Food Consumption Behavior in People with High Blood Sugar Levels in Tanjung Anom - Derang, Imelda; Ginting, Friska Sri Handayani Br; Ginting, Agustaria; Rupang, Ernita Rante (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Food consumption behavior is a form of application of eating habits that are influenced by two factors, namely knowledge and attitudes towards food. Food consumption behavior, like any other behavior toward oneself, family or society, is influenced by opinions and other factors related to right action. This study aims to determine the behavioral characteristics of risky food consumption in people with High Blood Sugar Levels in Tanjung Anom . This research is a quantitative research with a descriptive research design. The study population was 10,087 people, where the samples taken were 68 people with the Accidental Sampling technique with the sample criteria being people with increased Blood Sugar Levels. From the results of the study, the majority of people who experienced an increase in Blood Sugar Levels in the age group of 46-55 years with a total of 21 people (30.9%), based on gender, the most were female as many as 60 people (88.2%), respondent data based on the most education, namely high school / high school education as many as 29 people (42.6% and based on the most jobs was IRT, which was 37 people (54.4%). It is expected that the community will choose healthy foods to reduce the increase in KGD in the people of Tanjung Anom hamlet III.